Meme-ing Electoral Participation - Benita Heiskanen (European Journal of American Studies)
In February 2016, the Washington Post characterized the presidential primaries as “the most-memed election in U.S. history.” During the election year, meme-ing related to the major candidates became hugely popular and engaged various groups of people who were not ordinarily involved in bipartisan political processes. As brief, to the point, and quickly modifiable visual-textual messages, Internet memes were a particularly apt way to illustrate the most contested hot-button issues that emerged during the 2016 presidential race. This article considers the phenomenon of meme-ing in relation to both the Republican and Democratic campaigns. In particular, it focuses on memes that called attention to the candidates’ contradictory or incongruous statements critiquing their policy positions. The article demonstrates the ways in which memes spoke to the intersection of electoral activism and cultural representations in several ways: they enabled users to rapidly take a stand on and react to developing political events in real time; they provided alternative parallel discourses to mainstream media viewpoints; and they enabled mobilizing voters outside of official political discourses. During the 2016 campaign, meme-ing served as an example of a politico-cultural discourse that exemplified the unusual election year in ways that conventional political analysis alone was not able to capture.